Recruitment Capabilities and Attractive Compensation in Supporting of the Employee Retention Paradigm - Dipa Teruna; Tedy Ardiansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Generally, employees who have high skills always accept offers from other companies or what we call